Atrial Fibrillation Recurrence and Peri-Procedural Complication Rates in nMARQ vs. Conventional Ablation Techniques: A Systematic Review and Meta-Analysis - Li, Ka H. C.; Dong, Mei; Gong, Mengqi; Bazoukis, George; Lakhani, Ishan; Ting, Yan Y.; Wong, Sunny H.; Li, Guangping; Wu, William K. K.; Vassiliou, Vassilios S.; Wong, Martin C. S.; Letsas, Konstantinos; et al. (Frontiers in Physiology, 2018)
Background and Objectives: Atrial fibrillation is a common abnormal cardiac rhythm caused by disorganized electrical impulses. AF which is not refractory to antiarrhythmic management is often treated with catheter ablation. Recently a novel ablation system (nMARQ) was introduced for PV isolation. However, there has not been a systematic review of its efficacy or safety compared to traditional ablation techniques. Therefore, we conducted this meta-analysis on the nMARQ ablation system. Methods: PubMed and EMBASE were searched up until 1st of September 2017 for articles on nMARQ. A total of 136 studies were found, and after screening, 12 studies were included in this meta-analysis. Results: Our meta-analysis shows that the use of nMARQ was associated with higher odds of AF non-recurrence (n=1123, odds ratio =6.79, 95% confidence interval 4.01-11.50; P<0.05; I2 took a value of 83%). Moreover, the recurrence rate of AF using nMARQ was not significantly different from that of traditional ablation procedures (n=158 vs. 196; OR=0.97, 95% confidence interval:0.59-1.61). No significant difference in complication rates was observed between these groups (RR: 0.86; 95% CI: 0.37-1.99; P>0.05). There were four reported mortalities in the nMARQ group compared to none in the conventional ablation group (relative risk: 1.58; 95% CI: 0.09-29.24; P>0.05). Conclusions: AF recurrence rates are comparable between nMARQ and conventional ablation techniques. Although general complication rates are similar for both groups, the higher mortality with nMARQ suggests that conventional techniques should be used for resistant AF until improved safety profiles of nMARQ can be demonstrated.